The Mutational Landscape of Acute Promyelocytic Leukemia Reveals an Interacting Network of Co-Occurrences and Recurrent Mutations. - Ibáñez, Mariam; Carbonell-Caballero, José; García-Alonso, Luz; Such, Esperanza; Jiménez-Almazán, Jorge; Vidal, Enrique; Barragán, Eva; López-Pavía, María; LLop, Marta; Martín, Iván; Gómez-Seguí, Inés; Montesinos, Pau; et al. (PLoS One, 2016)
Preliminary Acute Promyelocytic Leukemia (APL) whole exome sequencing (WES) studies have identified a huge number of somatic mutations affecting more than a hundred different genes mainly in a non-recurrent manner, suggesting that APL is a heterogeneous disease with secondary relevant changes not yet defined. To extend our knowledge of subtle genetic alterations involved in APL that might cooperate with PML/RARA in the leukemogenic process, we performed a comprehensive analysis of somatic mutations in APL combining WES with sequencing of a custom panel of targeted genes by next-generation sequencing. To select a reduced subset of high confidence candidate driver genes, further in silico analysis were carried out. After prioritization and network analysis we found recurrent deleterious mutations in 8 individual genes (STAG2, U2AF1, SMC1A, USP9X, IKZF1, LYN, MYCBP2 and PTPN11) with a strong potential of being involved in APL pathogenesis. Our network analysis of multiple mutations provides a reliable approach to prioritize genes for additional analysis, improving our knowledge of the leukemogenesis interactome. Additionally, we have defined a functional module in the interactome of APL. The hypothesis is that the number, or the specific combinations, of mutations harbored in each patient might not be as important as the disturbance caused in biological key functions, triggered by several not necessarily recurrent mutations.
Keywords: Exome; Gene Regulatory Networks; Genome, Human; Humans; INDEL Mutation; Leukemia, Promyelocytic, Acute; mutation; Mutation Rate; Polymorphism, Single Nucleotide; Reproducibility of Results

The role of the interactome in the maintenance of deleterious variability in human populations. - García-Alonso, Luz; Jiménez-Almazán, Jorge; Carbonell-Caballero, José; Vela-Boza, Alicia; Santoyo-López, Javier; Antiňolo, Guillermo; Dopazo, Joaquin (Mol Syst Biol, 2014)
Recent genomic projects have revealed the existence of an unexpectedly large amount of deleterious variability in the human genome. Several hypotheses have been proposed to explain such an apparently high mutational load. However, the mechanisms by which deleterious mutations in some genes cause a pathological effect but are apparently innocuous in other genes remain largely unknown. This study searched for deleterious variants in the 1,000 genomes populations, as well as in a newly sequenced population of 252 healthy Spanish individuals. In addition, variants causative of monogenic diseases and somatic variants from 41 chronic lymphocytic leukaemia patients were analysed. The deleterious variants found were analysed in the context of the interactome to understand the role of network topology in the maintenance of the observed mutational load. Our results suggest that one of the mechanisms whereby the effect of these deleterious variants on the phenotype is suppressed could be related to the configuration of the protein interaction network. Most of the deleterious variants observed in healthy individuals are concentrated in peripheral regions of the interactome, in combinations that preserve their connectivity, and have a marginal effect on interactome integrity. On the contrary, likely pathogenic cancer somatic deleterious variants tend to occur in internal regions of the interactome, often with associated structural consequences. Finally, variants causative of monogenic diseases seem to occupy an intermediate position. Our observations suggest that the real pathological potential of a variant might be more a systems property rather than an intrinsic property of individual proteins.
Keywords: Alleles; Exome; Gene Library; Genetic Variation; Genetics, Population; Genome, Human; Genomics; Humans; Models, Genetic; mutation; Phenotype; Protein Conformation; Protein Interaction Maps; Sequence Analysis, DNA; Whites

Exome sequencing identifies a new mutation in SERAC1 in a patient with 3-methylglutaconic aciduria. - Tort, Frederic; García-Silva, María Teresa; Ferrer-Cortès, Xènia; Navarro-Sastre, Aleix; Garcia-Villoria, Judith; Coll, Maria Josep; Vidal, Enrique; Jiménez-Almazán, Jorge; Dopazo, Joaquin; Briones, Paz; Elpeleg, Orly; Ribes, Antonia (Mol Genet Metab, 2013)
3-Methylglutaconic aciduria (3-MGA-uria) is a heterogeneous group of syndromes characterized by an increased excretion of 3-methylglutaconic and 3-methylglutaric acids. Five types of 3-MGA-uria (I to V) with different clinical presentations have been described. Causative mutations in TAZ, OPA3, DNAJC19, ATP12, ATP5E, and TMEM70 have been identified. After excluding the known genetic causes of 3-MGA-uria we used exome sequencing to investigate a patient with Leigh syndrome and 3-MGA-uria. We identified a homozygous variant in SERAC1 (c.202C>T; p.Arg68*), that generates a premature stop codon at position 68 of SERAC1 protein. Western blot analysis in patient's fibroblasts showed a complete absence of SERAC1 that was consistent with the prediction of a truncated protein and supports the pathogenic role of the mutation. During the course of this project a parallel study identified mutations in SERAC1 as the genetic cause of the disease in 15 patients with MEGDEL syndrome, which was compatible with the clinical and biochemical phenotypes of the patient described here. In addition, our patient developed microcephaly and optic atrophy, two features not previously reported in MEGDEL syndrome. We highlight the usefulness of exome sequencing to reveal the genetic bases of human rare diseases even if only one affected individual is available.
Keywords: Adolescent; Adult; Carboxylic Ester Hydrolases; Child; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Infant; Male; Metabolism, Inborn Errors; mutation